2020
DOI: 10.1088/1757-899x/788/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mechanical properties of Copper Brazed by laser surface modification

Abstract: Nowadays, laser surface modification (LSM) has become the most advance technique for improving the surface properties for joining methods. This is due to its advantages such as cleaner, precise, more reliable and provides exact control compare to other surface modification techniques. This technique also applicable on wide range of materials, such as metal/alloy, ceramic and polymer. Brazing is a metal-joining process in which two or more metal items are joint together by melting and flowing a filler metal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It can be supported by the finding from A Sulaiman, who reported that when a higher laser power usage is applied to modify the metal's surface, bigger and deeper microgrooves will be produced hence, increasing the surface roughness [14]. Besides, the increment in laser power was attributed to the increase in energy radiated will also affect the melt pool homogeneity and size, inducing larger melt tracks, hence producing rough surface [15].…”
Section: Effect Of Laser Power On Surface Roughnessmentioning
confidence: 69%
“…It can be supported by the finding from A Sulaiman, who reported that when a higher laser power usage is applied to modify the metal's surface, bigger and deeper microgrooves will be produced hence, increasing the surface roughness [14]. Besides, the increment in laser power was attributed to the increase in energy radiated will also affect the melt pool homogeneity and size, inducing larger melt tracks, hence producing rough surface [15].…”
Section: Effect Of Laser Power On Surface Roughnessmentioning
confidence: 69%
“…For future works, the level of the hatching distance could be optimised, and additional parameters can be analysed. Laser surface modification of engineering alloys are now finding great applications in hardening [19] and brazing technology [20], and it would be wise to see their effect on other applications as well.…”
Section: Discussionmentioning
confidence: 99%
“…As nanosecond laser technology is versatile and simple to shape, many parameters must, of course, need to be optimised to achieve the best machining performance. Laser power [5], pulse duration [6], frequency [7], scan speed, hatching parameters and scan loop [8] are among the laser parameters that are often studied.…”
Section: Introductionmentioning
confidence: 99%